What do the basal ganglia do? - Brown, P; Marsden, C (1998)
We propose that the basal ganglia support a basic attentional mechanism operating to bind input to output in the executive forebrain. Such focused attention provides the automatic link between voluntary effort, sensory input, and the calling up and operation of a sequence of motor programmes or thoughts. The physiological basis for this attentional mechanism may lie in the tendency of distributed, but related, cortical activities to synchronise in the gamma (30 to 50 Hz) band, as occurs in the visual cortex. Coherent and synchronised elements are more effective when convergence occurs during successive stages of processing, and in this way may come together to give the one gestalt or action. We suggest that the basal ganglia have a major role in facilitating this aspect of neuronal processing in the forebrain, and that loss of this function contributes to parkinsonism and abulia.